Effects of selenium-enriched yeast dietary supplementation on egg quality, gut morphology and caecal microflora of laying hens - Ruili Li; Jiewei Liu; Minxiao Liu; Mingzhi Liang; Zengguang Wang; Yufen Sha; Huiwen Ma; Yafeng Lin; Baohua Li; Jinming You; Lei Zhang; Ming Qin (Animal Biotechnology)
Selenium (Se) is an essential micronutrient for humans and animals and is a powerful antioxidant that can promote reproductive and immune functions. The purpose of this study was to evaluate the effects of supplemental dietary selenium-enriched yeast (SeY) on egg quality, gut morphology and microflora in laying hens. In total, 100 HY-Line Brown laying hens (45-week old) were randomly allocated to two groups with 10 replicates and fed either a basal diet (without Se supplementation) or a basal diet containing 0.2 mg/kg Se in the form of SeY for 8 weeks. The Se supplementation did not have a significant effect on egg quality and intestinal morphology of laying hens. Based on the 16S rRNA sequencing, SeY dietary supplementation effectively modulated the cecal microbiota structure. An alpha diversity analysis demonstrated that birds fed 100 mg/kg SeY had a higher cecal bacterial diversity. SeY dietary addition elevated Erysipelotrichia (class), Lachnospiraceae (family), Erysipelotrichaceae (family) and Ruminococcus_torques_group (genus; p < .05). Analysis of microbial community-level phenotypes revealed that SeY supplementation decreased the microorganism abundance of facultatively anaerobic and potentially pathogenic phenotypes. Overall, SeY supplementation cannot significantly improve intestinal morphology; however, it modulated the composition of cecal microbiota toward a healthier gut.